2020
DOI: 10.1002/adtp.202000136
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine for the Treatment of Advanced Prostate Cancer

Abstract: Current prostate cancer (PCa) treatment options include hormonal therapy, chemotherapy, immunotherapy, and radiotherapy; however, a lack of targeting and overall efficiency has failed to improve survival rates or reduce unwanted side‐effects in advanced stage PCa patients. The modification of existing therapeutics, including their reformulation as nanomedicines, can increase stability in plasma, enhance tumor targeting, and improve pharmacokinetics to foster improvements in patient outcomes. This review now de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 335 publications
(443 reference statements)
0
2
0
Order By: Relevance
“…19-A). One prominent approach is immunotherapy, which aims to activate the patient's immune system to recognize and attack cancer cells within the TME [190]. Checkpoint inhibitors, such as PD-1 and CTLA-4 inhibitors, have shown remarkable success in this regard [241].…”
Section: Methods Developed With the Express Purpose Of Combating Tmementioning
confidence: 99%
See 2 more Smart Citations
“…19-A). One prominent approach is immunotherapy, which aims to activate the patient's immune system to recognize and attack cancer cells within the TME [190]. Checkpoint inhibitors, such as PD-1 and CTLA-4 inhibitors, have shown remarkable success in this regard [241].…”
Section: Methods Developed With the Express Purpose Of Combating Tmementioning
confidence: 99%
“…Angiogenesis inhibitors, like anti-VEGF drugs, are employed to hinder the formation of new blood vessels within the tumor. Furthermore, the development of targeted therapies that disrupt specific signaling pathways crucial for TME maintenance, such as the PI3K/ AKT/mTOR pathway, holds promise in altering the TME to make it less hospitable to cancer cells [190]. Collectively, these mechanisms offer a multifaceted approach to target the TME and improve the efficacy of cancer treatment, potentially leading to more effective and personalized therapeutic strategies [267].…”
Section: Methods Developed With the Express Purpose Of Combating Tmementioning
confidence: 99%
See 1 more Smart Citation
“…Administration of multiple therapeutic agents remains challenging, however, in this context nanotechnology applied to drug delivery can offer a series of advantages such as the possibility to combine in a unique carrier system more than one therapeutic agent and to increase the bioavailability of the single components. [7][8][9][10] Furthermore, it has been reported that several nanocarriers can afford implementation of classical chemotherapy with other types of treatment like photodynamic therapy (PDT). [11][12][13][14][15] Combination therapy aims at the synergic action of different therapeutics targeting more than one metabolic pathway in order to maximize the impact of the treatment and eventually improve the therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Nanomedicines have emerged as exciting new therapeutic modalities for unmet clinical needs, and in this study, we focused on the potential of polymer therapeutics, particularly polymer-drug conjugates (PDCs), for the treatment of advanced metastatic PCa. [7] PDCs are defined as macromolecular complexes in which a drug is covalently bound to a water-soluble polymeric carrier. [8] Compared to conventional small moleculebased therapies, PDCs have several advantages for cancer therapy, including i) enhanced aqueous solubility, ii) higher drug loading capacity, iii) prolonged blood circulation times and, therefore, improved bioavailability and biodistribution via the so-called enhanced permeability and retention (EPR) effect, [9] and consequently, iv) reduced toxicity for healthy tissues and v) increased anti-tumor efficacy.…”
Section: Introductionmentioning
confidence: 99%